Analisis Tingkat Plagiarisme Manuskrip Hasil Penelitian Mahasiswa Dengan Menggunakan Software Turnitin di Perpustakaan Fakultas Keperawatan Universitas Riau - Thamrin Hasan; Rekhman; Asmawati (Perpustakaan Universitas Riau, 2021)
This study discusses the level of plagiarism in the results of student research in the Faculty of Nursing Library, Riau University. This study aims to determine the level of plagiarism (similarity index) of manuscripts using Turnitin software. The research method used is a quantitative method with a descriptive approach. Data collection techniques used documentation techniques. Method of data analysis using Turnitin software. The results showed that the lowest level of similarity index was 26%, and the highest was 69%. Of the 57 data samples analyzed, only 3 manuscripts or 5.26% resulted in a similarity index level of less than 30%. That is, there are only 3 manuscripts that can be declared a light level of plagiarism. On the other hand, there are 54 manuscripts or 97.74%, the level of similarity index is between 30% - 70%. This means that there are 54 manuscripts that have a moderate level of plagiarism. Then there is not a single manuscript that has a similarity index level in the heavy category. Overall, the analyzed manuscript document data obtained an average similarity index of 46%. This means that, as a whole, the level of plagiarism is in the moderate category. Then, the source most or most frequently used in making manuscripts of research results comes from media.neliti.com. This source was detected as many as 54 manuscripts, with an average similarity of 6.44%. Then, the second most frequently used source is from www.scribd.com, which is as many as 53 manuscripts with an average similarity of 4.97%. While the third most frequently used source is from jom.unri.ac.id, which is 27 manuscripts with an average similarity of 5.57%.